2018
DOI: 10.1021/acs.est.8b03910
|View full text |Cite
|
Sign up to set email alerts
|

Fe(II)-Catalyzed Ligand-Controlled Dissolution of Iron(hydr)oxides

Abstract: Dissolution of iron(III)phases is a key process in soils, surface waters and the ocean. Previous studies found that traces of Fe(II) can greatly increase ligand controlled dissolution rates at acidic pH, but the extent that this also occurs at circumneutral pH and what mechanisms are involved are not known. We addressed these questions with infrared spectroscopy and 57 Fe isotope exchange experiments with lepidocrocite (Lp) and 50 µM ethylenediaminetetraacetate (EDTA) at pH 6 and 7. Addition of 0.2-10 µM Fe(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 51 publications
4
21
0
Order By: Relevance
“…Fenton reaction between Fe­(II) and Fe­(III) of goethite in the presence of O 2 may occur and produce reactive oxidizing species that could also oxidize HA. , Dissolved Fe from goethite, likely Fe­(II)-ligand complexes, was detected by UV–vis spectroscopy under anoxic (Figure S7) but not oxic conditions, indicating reductive dissolution of goethite by HA. However, in the control system with HA and goethite at pH 8 under oxic conditions, only a small amount of LMW acids was produced (Control 2 in Figure a), suggesting that Fenton reaction, if occurring, only occurred to a very low extent. The fact that dissolved Fe-ligand complexes were detected under only anoxic but not oxic conditions may be ascribed to oxidation of Fe­(II) by O 2 to form Fe­(III) solid phases or Fe­(III)-ligand complexes. ,, Overall, the oxidation of HA by goethite does not affect our conclusion that Mn­(II) oxidation by O 2 is the major mechanism responsible for the greatly enhanced HA oxidation in the presence of Mn­(II).…”
Section: Discussionmentioning
confidence: 65%
“…Fenton reaction between Fe­(II) and Fe­(III) of goethite in the presence of O 2 may occur and produce reactive oxidizing species that could also oxidize HA. , Dissolved Fe from goethite, likely Fe­(II)-ligand complexes, was detected by UV–vis spectroscopy under anoxic (Figure S7) but not oxic conditions, indicating reductive dissolution of goethite by HA. However, in the control system with HA and goethite at pH 8 under oxic conditions, only a small amount of LMW acids was produced (Control 2 in Figure a), suggesting that Fenton reaction, if occurring, only occurred to a very low extent. The fact that dissolved Fe-ligand complexes were detected under only anoxic but not oxic conditions may be ascribed to oxidation of Fe­(II) by O 2 to form Fe­(III) solid phases or Fe­(III)-ligand complexes. ,, Overall, the oxidation of HA by goethite does not affect our conclusion that Mn­(II) oxidation by O 2 is the major mechanism responsible for the greatly enhanced HA oxidation in the presence of Mn­(II).…”
Section: Discussionmentioning
confidence: 65%
“…The dissolution of iron from hematite and other Fe minerals mainly follows three mechanisms: proton-promoted, ligand-controlled, and reductive dissolution. ,,, A large quantity of non-Fe-bearing metal oxides in mineral dust allows for them to compete for acid or organic anions in the deliquescent layer and, thus, to influence iron dissolution. Previous studies on gas–solid interactions report that adsorption of acid anions onto mineral dust components, such as Al 2 O 3 and TiO 2 , results in solvated ions under humid conditions. , Moreover, some of these interactions may even yield secondary products that passivate or activate the dust surface or modify crystal phases.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies demonstrated that the reductant reduces Fe(III) to Fe(II), which can catalyze ligand-controlled dissolution at sub-micromolar Fe(II) concentrations, for a variety of Fe(hydr)oxide minerals and over a broad environmentally relevant pH range [28]. These findings were supported by ATR-FTIR analysis and isotope exchange experiments [29].…”
Section: Introductionmentioning
confidence: 87%